Applying General Rules of Halakhah in Halakhic Exegesis - Zur, Uri (The review of rabbinic Judaism, 2015)
Rather than a sequence of indeterminate differences of legal opinion, the Halakhic texts in the Bavli as it has reached us incorporate a series of meta-principles stated as general rules for resolving the debates of the Tannaim. The present article focuses on the maxims of Halakhic arbitration cited in the Bavli in the name of R. Yohanan. Formulated as unequivocal, definitive prescriptions, R. Yohanan’s maxims for the arbitration of Tannaitic disputes are actually of debatable applicability; particular instances of Halakhah running counter to the general principles underscore this ambiguity. The ambiguity is both perplexing and a passageway to insight. Can any methodic classification of approaches to it be produced to facilitate a hermeneutic for reading both R. Yohanan’s imperatives and the cases of deviation from them that the Bavli preserves? The present article takes up the challenge.